Software development to calculate resistance to ground for different rods/wire configuration - Aloysius Pallis A/L Gerad (2023)
This project is solely to develop software that will be able to calculate resistance to ground for different configurations of rods/wire. The work involves coding the software and also carrying out experiments to verify the formulas to calculate resistance to ground that is coded into the software.